Carbon mitigation and climate change through forest management - Munster, Jennifer P. (New York : Nova Science Publishers, Inc., 2011)
"Global climate change is a widespread and growing concern that has led to extensive international discussions and negotiations. Responses to this concern have focused on reducing emissions of greenhouse gases, especially carbon dioxide, and on measuring carbon absorbed by and stored in forests, soils, and oceans. One option for slowing the rise of greenhouse gas concentrations in the atmosphere, and thus possible climate change, is to increase the amount of carbon removed by and stored in forests. This book examines the issues of carbon sequestration in forests. Also discussed are the existing federal programs that could affect forest carbon sequestration."--Pub. desc.
Engaging Western Landowners in Climate Change Mitigation: A Guide to Carbon-Oriented Forest and Range Management and Carbon Market Opportunities / David D. Diaz, Susan Charnley, Hannah Gosnell -- Carbon Sequestration in Forests / Ross W. Gorte -- Estimates of Carbon Mitigation Potential from Agricultural and Forestry Activities / Renee Johnson, Jonathan L. Ramseur, Ross W. Gorte.
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Carbon sequestration; Climate change mitigation; Forest management -- Environmental aspects; Piégeage du carbone; Climat -- Changements -- Atténuation.; Forêts -- Gestion -- Aspect de l'environnement.; TECHNOLOGY & ENGINEERING / Environmental / General; Carbon sequestration; Climate change mitigation; Forest management -- Environmental aspects